Penggunaan Metode Berkisah Terhadap Efektivitas Pembelajaran Daring Pada Mata Pelajaran Sejarah Kebudayaan Islam Kelas VIII D MTs Daarul Uluum PUI Majalengka - Qonitat Hafizhoh; Syafa'atun Nahriyah (Al-Mau'izhoh, 2021)
To improve the quality of sustainable education during the Covid-19 outbreak, it is necessary to have innovative innovations in the learning system and fun learning methods for students. The online learning system is one of the new innovations for several public and private schools, especially at the Elementary School and Junior High School (SMP) levels. With the change, teachers are looking for new innovations so that methods that were originally done offline can be put online. The storytelling method is the choice of various existing learning methods that can be combined with online learning systems. This study was carried out with the aim of scientifically analyzing the influence of storytelling methods on online learning in the subject of Islamic Cultural History (SKI) class VIII D MTs Daarul Uluum PUI Majalengka . Based on the survey results, the researchers hope that by using the storytelling method, online learning will be more effective and fun for students, but there are still obstacles in the application of a shorter and limited time. This can be seen from the following indicators: 1) Motivation for Islamic History, 2) Love for Islamic Culture and Civilization, 3) Explanation of Interesting Stories, 4) Exemplary Historical Figures, and 5) Media Supporting Storytelling .The research method that the researcher uses is descriptive quantitative method, namely the research is carried out by looking for numbers seen from the results of questionnaires to students and teachers of the subject, so it is hoped that the research carried out serves to find out, study and describe the influence between variables. The population in this study was the class VIII students of MTs Daarul Uluum PUI, Majalengka amounting to 30 people. The research sample was taken from the population using the census/total sampling method. Thus the number of samples in the study was 30 people. The results showed that there was a good influence between the storytelling method on online learning with a correlation number of 0.523 and a coefficient of determination of 52%. The linkage factor given is in the medium category and there are still 48% of other factors that are related to SKI online learning at MTs Daarul Uluum PUI, Majalengka Kulon Village, Majalengka Regency. Of the 48% of these other factors are the influence of other methods and the use or utilization of other applications that have been implemented in other schools.  Keywords: Storytelling Method, Online Learning